2013
DOI: 10.1161/circinterventions.113.000814
|View full text |Cite
|
Sign up to set email alerts
|

Operator’s Experience Is the Most Efficient Embolic Protection Device for Carotid Artery Stenting

Abstract: Stabile and Esposito Operator's Experience Determines CAS Outcomes 497reported a large unpredictability of data (the incidence of new postprocedural DW-MRI detected lesions ranged from 15.8% to 87.1%). Recent bench work evaluation of these 2 different filters demonstrated that they have a comparable ability to capture embolic particle and makes really difficult to explain that data variability. 10CAS outcomes are influenced by operators experience on the procedure itself and on the use of specific EPD. 11,12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…We appreciated the editorial by Stabile and Esposito, 1 where the authors made an extensive discussion on conflicting results between our trial and others previously published. [2][3][4] The authors' conjectures on these studies suggest that operator experience with carotid artery stenting procedures seems to be the best brain embolic protective factor.…”
Section: To the Editormentioning
confidence: 85%
See 2 more Smart Citations
“…We appreciated the editorial by Stabile and Esposito, 1 where the authors made an extensive discussion on conflicting results between our trial and others previously published. [2][3][4] The authors' conjectures on these studies suggest that operator experience with carotid artery stenting procedures seems to be the best brain embolic protective factor.…”
Section: To the Editormentioning
confidence: 85%
“…The authors argued that our reported differences between flow-reversal and filter procedure times (22.41 versus 16.78 minutes; P<0.001) were in accordance with the lower operator's experience with the flow-reversal device. 1 However, in previous trials, the mean procedure times were also significantly longer with proximal than with distal protection devices 30 versus 22 minutes (P=0.003) and 29.5 versus 24.2 minutes (P=0.051) reported by Bijuklic et al 4 and Cano et al, 5 respectively, whereas Montorsi et al 3 did not report procedure times with the proximal protection group. Moreover, it is noteworthy that our mean procedure time with flow-reversal (22.41 minutes) was the shortest, which clearly contradicts Stabile's opinion.…”
Section: To the Editormentioning
confidence: 85%
See 1 more Smart Citation
“…The limited compatibility of contemporary EPS with the array of 0.014″ guidewires may be reflected in the limitations of present CAS: (1) an extended operator's learning curve [17][18][19] ; (2) device-specific learning curve. Each EPD requires an individual learning curve; and (3) relationship between thromboembolic events and complex vascular geometries and high-risk lesion morphological features.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple prospective studies and meta‐analyses have shown that higher‐volume operators (i.e., ≥ 6 cases per year) demonstrate lower rates of adverse complications, including stroke . At our hospital, there are three departments with privileges to perform CAS: IC, IR, and NS.…”
Section: Discussionmentioning
confidence: 99%